Health and the running body: Notes from an ethnography. (February 2016) - Shipway, Richard; Holloway, Immy
This article aims to develop one of the major themes from an ethnographic study of the culture of distance running – the desire for health and fitness. Research was undertaken over a 2-year period using a variety of flexible qualitative data sources, most notably observation and in-depth interviews. The body, especially the 'running body', is seen by participants in this study as a source of health and well-being and affirmation of their identity. The results highlight the various contradictions and tensions that emerged whilst exploring the behaviour of distance runners in their desire to achieve a healthy body and mind.